US-Bulgarian Relations 1950-1959 - Mahawish, Lect. Mohamed Abboud (Thi Qar Arts Journal, 2022)
The research dealt with the US-Bulgarian relations 1950-1959, after a series of harassment between 1947-1949, which the American commission in Sofia was subjected to, the last of which was the accusation of Ambassador Heath and the demand for his departure, which prompted the US government to issue a warning to Bulgaria to withdraw the charges, and not The official Bulgarian response, the American-Bulgarian relations were severed in 1950, and the consequent American retaliatory reactions by isolating Bulgaria internationally, but after the death of the leader of the Soviet Union Stalin in 1953, and after that there was a change in Soviet and Bulgarian policy, so Bulgaria has made efforts since In 1953 to resume relations, but these attempts were not crowned with success, except in 1959 with Polish mediation.